PENDIDIKAN ISLAM MASA PERTENGAHAN (Studi Historis Pendidikan Di Kerajaan Usmani, Kerajaan Safawi Dan Kerajaan Mughal) - Aniroh Aniroh (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2021)
The Middle Ages in the Periodation of Islamic History refers to the existence of three major kingdoms, namely the Ottoman Empire in Turkey, the Safavid Empire in Persia and the Mughal Empire in India.  The three kingdoms in the Middle Ages illustrate the shift in non-Arab domination after the Arab domination in the classical period. In general, the middle period is considered a period of decline.  However, historical facts about education in the three kingdoms give a picture of development and progress.  During the Ottoman era, madrasas were encouraged to study a variety of sciences.  Many educational institutions emerged during the reign of the Ottoman Empire, one of which was the madrasa.  The first Usmani Madrasah was founded in Izmir in 1331 AD.The state of education in the Safavid Kingdom is shown by a very thick academic atmosphere.  Among them is shown by the existence of tolerance and freedom of expression.  Despite the rigors of indoctrination in the period of Shah Abbas II, freedom of liberal thought once gained momentum. In the Mughal Empire, education received considerable attention. The kingdom encourages mosques as places of religious study for the community other than as places of worship.  Mosques have provided scholars who will teach various branches of religious knowledge.  In fact, the mosque has also provided a special room for students who want to stay in the mosque while attending education.Keywords: Middle Ages, Education, Islam, Ottoman Empire, Safavid Kingdom, Mughal Empire.